Faktor-Faktor Penyebab Tumbuhnya Permukiman Kumuh di Kelurahan Tuan Kentang Kota Palembang - Dwi Apriliani; Eni Heldayani; Budi Utomo; Heri Setianto (RUAS, 2022)
The high rate of population growth in the city of Palembang has an impact on the quality and quantity of its people. So that the high population causes an imbalance between the number of residents and the needs of their place to live which triggers the emergence of slum areas. This study aims to determine what factors cause the growth of slum settlements in Tuan Kentang Village, Jakabaring District, Palembang City. The object or informant in this study is the community of RT 27, Tuan Kentang Village. The research method used in this research is qualitative. The data collection techniques used are observation, questionnaires, and documentation. From the results of this study, Tuan Kentang Village, Jakabaring District is categorized as a slum area due to low accessibility, low facilities and infrastructure, inadequate sanitation, and low socioeconomic conditions.